2012
DOI: 10.3168/jds.2011-5173
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatics analysis of microRNA and putative target genes in bovine mammary tissue infected with Streptococcus uberis

Abstract: MicroRNA (miRNA) are small single-stranded noncoding RNA with important roles in regulating innate immunity in nonruminants via transcriptional and posttranscriptional mechanisms. Mastitis causes significant losses in the dairy industry and a wealth of large-scale mRNA expression data from mammary tissue have provided fundamental insights into the tissue adaptations to pathogens. We studied the expression of 14 miRNA (miR-10a, -15b, -16a, -17, -21, -31, -145, -146a, -146b, -155, -181a, -205, -221, and -223) as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
70
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(78 citation statements)
references
References 57 publications
6
70
0
2
Order By: Relevance
“…In order to further explore the mechanism of IGF-1 variation in patients with sepsis, miRNA-1 levels were analyzed in patients with sepsis, since IGF-1 is the target gene of miRNA-1 according to previous studies (28,29). The present study demonstrated that patients with sepsis had higher plasma miRNA-1 levels, which was negatively correlated with the IGF-1.…”
Section: Discussionmentioning
confidence: 57%
“…In order to further explore the mechanism of IGF-1 variation in patients with sepsis, miRNA-1 levels were analyzed in patients with sepsis, since IGF-1 is the target gene of miRNA-1 according to previous studies (28,29). The present study demonstrated that patients with sepsis had higher plasma miRNA-1 levels, which was negatively correlated with the IGF-1.…”
Section: Discussionmentioning
confidence: 57%
“…Our previous study has already shown an activation of TLR4 signalling pathway and dysregulation of intracellular TLR4-related miRNAs, such as miR-146a/b, in PBMCs obtained from patients with CAD [5]. A number of identified miRNAs, such as miR-146, miR181a, miR-151, miR-31, miR-223, miR-145 and miR-155, are known to regulate various biological pathways including the immune system through the development and function of immune components [30]. It has also been reported that some miRNAs bound as ligands to receptors of the TLR family and thus controlled tumour immune response [31].…”
Section: Discussionmentioning
confidence: 98%
“…Naeem et al examined a panel of 14 miRNAs from mammary tissue biopsied during an in vivo intra-mammary Streptococcus uberis infection (46). Four of the fourteen miRNAs were found to undergo differential expression (Table 1).…”
Section: Role Of the Mirnas In The Bovine Immune Systemmentioning
confidence: 99%